Chapter 6: Architectural competitions as lab – a study on Souto de Moura’s competition entries - Guilherme, Pedro (2013)
Abstract International competitions reflect the architect’s personal design beyond controlled systems of social relations, comfort zones, age, gender or even expertise, in a fast and risky sublimation process. At the same time they generate publicity and a public recognition which may surpasses the investments in time, energy and financial resources. Based on the work of the 2011 Pritzker laureate – Portuguese architect Eduardo Souto de Moura – we put forward the hypothesis that international competitions act as an intersection between research and practice evolving through the nature of individual architecture. Souto de Moura follows Alvaro Siza Vieira and the Oporto’s School design practice. From 1979 to 2010 Souto de Moura submitted 50 competition entries, more than half international, of which 26 competitions were realized between 2007 and 2010. International competitions, besides acting as a refraction of a working method for a specific proposal provide an important resource for personal reflective practice and are seldom considered, compiled or jointly analysed. This paper will collect, document and outline the epistemology of the professional practice associated to the phenomenon of internationalization of this Portuguese architect. We will illustrate two competitions – “Salzburg Hotel” (1987-89) and “The Bank” (1993) – and one built project in Oporto – “Burgo Tower” (1991-95 Phase 1; 2003-04 Phase 2; 2007 Construction) – that share a progression of methodological imagery, clarity and innovation from primordial immateriality towards the built form. Souto de Moura’s work relentlessly and repeatedly searches for the solution that serves the program and the task at hand taking risks and challenges as stimulation for creativity, conveying reflection in theory and culture and, at the same time, remaining obsessive towards specific themes. Souto de Moura is permanently a scientist in a lab: satisfying client’s needs (or as acting as one), creating beauty, elegance and solving riddles, thus addressing competitions with qualified rhetoric. We conclude proposing that competitions provide a theoretical corpus of knowledge, besides what is specific and unique to each one individually, which infer the existence of an overlapping and intertwined, complex system of projects. Consequently, competitions constitute an optimised interface for the continuity of research for the architectural author where design statements put forward in proposals transcend the boundaries of the competition.